ECONOMIC DAMAGE CAUSED BY LACEBUG UPON CASSAVA ROOT AND FOLIAGE YIELD - FIALHO, Josefino de Freitas; VIEIRA, Eduardo Alano; PAULA-MORAES, Silvana Vieira de; SILVA, Marilia Santos; JUNQUEIRA, Nilton Tadeu Vilela (Scientia Agraria, 2009)
This research evaluated the economic damage of lacebug Vatiga illudens (Drake, 1922) (Hemiptera: Tingidae) upon cassava root and foliage yield. The experiments were carried out from 1994 to 1997 at the experimental area of Embrapa Cerrados, at the municipality of Planaltina - DF. The experimental design used was completely randomized blocks with four replications, in a scheme of subdivided plots. The plots consisted of varieties and in the subplots, randomized within each block, treatments with or without chemical control of lacebug were applied, mediated by sprays every two weeks with insecticides based on monocrotophos, dimetoate and vamidotion. The results obtained revealed that 1) high levels of lacebug nymph and adult infestation reduced cassava foliage and root yield and that 2) the sprays with insecticides resulted in increases of cassava foliage and root yield.